Analysis of industrial safety solutions that have transformed nuclear power by 2019. Issue 1 (September 2020) - Ivanov, A I; Egorov, M Yu; Stepashkina, A S; Kritchenkov, A S
Abstract: Safety of nuclear power plant elements relies on a range of national and international norms in the field of atomic energy use. Some of these norms is based not only on operation experience of nuclear units but also on statistics of failures among elements of nuclear facilities. Several well-known disasters occurred at nuclear power plants in USSR and Japan shows that its consequences may affect other countries. Therefore, failures analysis is performed not only nationally but also internationally – by International Atomic Energy Agency. However, different kind of failures: affecting and non-affecting safety of the nuclear unit still occur in Russia. This study is focused on statistical analysis of failures among nuclear power plant components with regards to its impact on unit safety assessed on the International Nuclear Event Scale. The analysis of industrial safety solutions that transformed the nuclear power industry was carried out for the period from 1992 to 2018. Though general decreasing trend can be noted within the that period, failures with safety impact occurred in 2 out of 3 years and non-impacting failures stabilized at around 61 events per year.